The Impact of AI and Digital Transformation in Shaping the Saudi Legal System - Nihaya Khalaf (International Journal of Law Research and Studies, 2025)
The digital economy is a disruptive force, altering industry, trade and society. As the premier financial and technological hub in the Middle East, Saudi Arabia is actively growing its digital economy by embracing Artificial Intelligence (AI) to enhance innovation, economic growth and productivity. This paper looks at the policy and legal framework of the digital transformation in the kingdom. In addressing the research question, the paper employs an interdisciplinary approach; this approach can help address complex technical issues related to technologies such as cybersecurity, data privacy and artificial intelligence. The paper is divided into two sections. The first one provides an overview of the governmental digital transformation policies for the health, finance and banking, and transportation sectors. The second part analyses the regulatory framework of this transformation highlighting the role of an enabling legal framework in the transition and its limit when looking at the continuous advancements of technologies.
Keywords: AI; Digital Transformation; Saudi Law; Policies and Legal Framework; Data Protection Law; Enabling Laws